2017
DOI: 10.1177/1744987117721596
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceived stress and compassion following a mindfulness meditation and self compassion training

Abstract: The pilot study explored the effects of a mindfulness based stress reduction (MBSR) intervention on nurses' perceived stress (PS) and compassion. A quasi experimental pre-test-post-test design was used. Nurses (n=90) working at three university teaching hospitals completed the Perceived Stress Scale (PSS) and Compassion Scale (CS) at the beginning of the MSBR intervention and 64 completed the scales at the end of the intervention. The 64 matched data sets were analysed using the ttest, Chi Square test and ANOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 52 publications
3
87
0
1
Order By: Relevance
“…Additionally, a separate regression analysis showed that changes in self-compassion significantly predicted positive changes in perceived stress. Contradicting these positive findings, some studies revealed nonsignificant changes in self-compassion among health care professionals participating in similar interventions (e.g., Brooker et al, 2013;Mahon, Mee, Brett, & Dowling, 2017;Romcevich, Reed, Flowers, Kemper, & Mahan, 2018). The current inconsistencies in the intervention methods (e.g., treatment type, length of intervention, home practice) and discrepancies in corresponding results throughout the literature make it difficult to draw conclusions about the efficacy of these programs.…”
Section: Promoting Self-compassion: Mindfulness-based Interventionsmentioning
confidence: 99%
“…Additionally, a separate regression analysis showed that changes in self-compassion significantly predicted positive changes in perceived stress. Contradicting these positive findings, some studies revealed nonsignificant changes in self-compassion among health care professionals participating in similar interventions (e.g., Brooker et al, 2013;Mahon, Mee, Brett, & Dowling, 2017;Romcevich, Reed, Flowers, Kemper, & Mahan, 2018). The current inconsistencies in the intervention methods (e.g., treatment type, length of intervention, home practice) and discrepancies in corresponding results throughout the literature make it difficult to draw conclusions about the efficacy of these programs.…”
Section: Promoting Self-compassion: Mindfulness-based Interventionsmentioning
confidence: 99%
“…Thirty-one studies included a mindfulness [62,66,69,93,126,133,135,[144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159] or meditation [87,[160][161][162][163][164][165][166] intervention (most often with the use of mindfulness-based stress reduction (MBSR) as a mindfulness program). Twenty-four studies [63,[70][71][72]86,96,105,151,160,162,[167][168][169][170][171][172][173][174][175]…”
Section: Mindfulness and Relaxationmentioning
confidence: 99%
“…Defined as the 'harmful reaction people have to undue pressures and demands placed on them at work' (Heath and Safety Executive (HSE), 2017:3), this type of stress is directly connected to a reduction of physical, psychological and mental wellbeing in staff (Hassard et al, 2017;Paparella, 2015). Its presence is implicated with increased levels of work-life imbalance (Clouston, 2014(Clouston, , 2015Pearson, 2015), burnout (Mahon et al, 2017;McTiernan and McDonald, 2015), compassion fatigue (Hunt et al, 2017;Maxwell, 2017;Mendes, 2017), anxiety and depression (HSE, 2017;Wang et al, 2015), reduced levels of productivity and low levels of satisfaction and engagement in the workplace (Royal College of Nursing (RCN), 2015).…”
Section: Introductionmentioning
confidence: 99%
“…the inability to feel emotionally for self or others (Maslach, Schaufeli and Leiter, 2001). Thus, it is closely linked to compassion fatigue, which is the inability to empathise or be caring or compassionate towards others due to emotional and psychological exhaustion (Hunt et al, 2017;Mahon et al, 2017). As purveyors of emotional labour nurses not only give of themselves therapeutically to patients but orchestrate emotions in order to meet workplace demands (Freshwater and Cahill, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation